Gender-specific sociodemographic and lifestyle factors associated with frailty status among Korean older adults - Subeen Kim; Haerang Lee; Nayeon Park; Eunseo Choi; Minji Kang (PLoS ONE, 2026)
This study aimed to identify gender-specific sociodemographic and lifestyle factors associated with frailty among Korean older adults. We conducted a cross-sectional analysis using data from the 2014–2019 Korean National Health and Nutrition Examination Survey, including 6,556 participants aged 65 years and older. Frailty was defined by the Fried phenotype. Multivariable logistic regression models were used to examine gender-specific associations between frailty and sociodemographic factors (age, education, marital status, household income, household type, and body mass index) as well as lifestyle factors (smoking, alcohol consumption, meals with family in the past year, energy intake, number of chronic diseases, and self-rated health status), with mutual adjustment for all listed covariates in a single fully adjusted model. The prevalence of frailty was 20.6% in women and 11.5% in men. Among women, current smoking [odds ratio (95% confidence interval), 2.22 (1.16–4.26)] and sharing meals with family in the morning [1.42 (1.05–1.93)] were associated with an increased risk of frailty. For men, high household income [0.51 (0.27–0.99)] and higher energy intake [>2,120 kcal; 0.49 (0.34–0.71)] were associated with a reduced risk of frailty. In both men and women, multiple chronic diseases and poor self-rated health were significantly associated with an increased risk of frailty. Frailty was associated with various sociodemographic and lifestyle characteristics in both men and women. The associations with several factors, such as smoking, meal patterns, and household income, differed by gender. This study highlights distinct gender-specific predictors of frailty among older Korean adults, emphasizing the need for tailored and integrated public health prevention strategies.